Quantitative Evaluation of the Efficiency of Two Component Inhibitors based on Polyelectrolytes - Ikramovich, Akbarov Khamdam (International Journal of Psychosocial Rehabilitation, 2020)
This paper considers the results of gravimetric determination of the degree of protection of two- component corrosion inhibitors based on polyelectrolytes and phosphorous-containing organic compounds synthesized by us and gives a quantitative assessment of their effectiveness. The paper investigated the influence of various factors on the effectiveness of inhibitors and found that two-component inhibitors effectively protect carbon steels from corrosion at high temperatures and exhibit a chemisorption mechanism of action.